Incidence of Incidental Gall Bladder Cancer and Role of Routine Histopathological Examination in Cholecystectomies Specimens for Benign Disease - Poudel, Rajesh; Shah, Anita (Journal of Nepal Health Research Council, 2020)
Background: Gallbladder cancer is the most common biliary tract cancer. Incidence rate of gall bladder cancer varies worldwide.  Most of the patient with gall bladder cancer remained asymptomatic until late. Preoperative early diagnosis of carcinoma of gallbladder is rare, occurring in fewer than 20% of patients. Role of routine histopathology for cholecystectomy specimen is debatable. Aim of this study is to find the incidence of incidental gall bladder cancer and determine whether routine histopathology of cholecystectomy specimen is required or not.Methods: This is a retrospective descriptive study carried out in Universal College of Medical Sciences, Bhairahawha, Nepal. Histopathology reports of all patients who had undergone cholecystectomies from June 2014 to September 2018 were reviewed. Patients’ information regarding inpatient number, age, sex, year of diagnosis, preoperative diagnosis, intraoperative findings, histopathology report and pathological staging were recorded. Data were entered and analyzed using Microsoft Excel version 14.Results: Total of 418 routine cholecystectomies were performed during this period. Seven cases of incidental gall bladder cancer were diagnosed. None of the patients had preoperative suspicion for malignancy. One patient had intraoperative suspicion of lesion.Conclusions: Incidence of incidental gallbladder cancer is 1.67%. It is recommended that routine histopathology of cholecystectomy specimen should be sent for early diagnosis and improve survival of patient with gall bladder cancer.Keywords: Cholecystectomy; gall bladder cancer; incidence, routine histopathology